Evolution of Payment Systems in the Digital Era: A Comprehensive Analysis of Mobile Payments, Contactless Technology and the Disruptive Potential of Cryptocurrencies on Traditional Payment Systems - Anbukarasi, M.; P.J, Sony (PT FORMOSA CENDEKIA GLOBAL, 2024)
Payment systems have seen a rapid change in the digital age, transforming how people and organizations perform financial transactions. An in-depth examination of the major advancements in payment systems in the digital age is provided in this research paper, with a particular emphasis on mobile payments, contactless technologies, and the prospective effects of cryptocurrencies on conventional payment methods. The study examines existing studies, new technological developments, and the implications for consumers and financial institutions. This article seeks to shed light on the potential future of digital payments by exploring the advantages and difficulties of these new payment systems